Interviewing: Principles and Practices - Stewart, Charles J.; Cash Jr., Willam B. (Boston, 2008)
This book is designed for courses in such departments as speech, communication, journal-ism, business, supervision, education, political science, nursing, criminology, and social work. It is also useful in workshops in various fields. We believe this book is of value to beginning students as well as to seasoned veterans because the principles, research, and techniques are changing rapidly in many fields. We have treated theory and research findings where applicable, but our primary concern is with principles and techniques that can be translated into immediate practice in and out of the classroom.
Keywords: Counseling; Employment Interviewing; Interviewing